An assessment of risk of iodine deficiency among pregnant women in Sarawak, Malaysia - Lim Kuang Kuay; Tan Beng Chin; Mohd Shaiful Azlan Kassim; Nur Azna Mahmud; Ruhaya Salle; Cheong Siew Man; Norazizah Ibrahim Wong; Chan Ying Ying; Tahir Aris (Intelektual Pustaka Media Utama, 2019)
Previous findings from a state-wide Iodine Deficiency Disorders (IDD) study among pregnant women (PW) in Sarawak indicated that PW are at risk of IDD and further assessment is needed. This paper describes the methodology used in conducting this study for an assessment of risk of iodine deficiency among pregnant women in Sarawak, Malaysia. A total of 30 maternal child health care clinics (MCHCs) were selected using probability proportional to population size (PPS) sampling technique. The PW sample size was calculated based on 95% confidence interval (CI), relative precision of 5%, design effect of 2, anticipated IDD prevalence of 65.0% and non-response rate of 20%. Thus, the total sample size required was 750 (25 respondents per selected MCHC). The WHO Expanded Programme on Immunization (EPI) surveys approach was used to randomly select the first respondent and subsequent respondents were chosen until the required number of PW was met. The required data were obtained through: face-to-face interviews (socio-demographic and food frequency questionnaire), clinical assessments (thyroid size, and hyper/hypothyroidism) and biochemical analysis (urine and blood serum). A total of 677 PW responded in the study with a response rate of 90.2%. Majority of the PW were at second gravida, aged 25-29 years old and of Malay ethnicity. The methodology used in this study was based on international guidelines which may provide state’s estimates. All the necessary steps were taken into consideration to ensure valid and reliable findings on current iodine status among PW.